Strategies for Overcoming Stereotypes and Prejudice in Multicultural Arabic Language Education Nātiq International Arabiyah Pare Kediri - Firdaus, Ahmad Yanif; Yusuf, Kamal; Hanifah, Umi (STIQ Amuntai, 2025)
In a multicultural educational environment, stereotypes and prejudices can be challenges that affect the effectiveness of learning, including in Arabic language education. Naatiq International Arabic Course Pare Kediri, as an Arabic language learning center that accommodates students from various cultural backgrounds, faces complex social dynamics. This study aims to identify the forms of stereotypes and prejudices that occur in Arabic language education at the Naatiq International Arabiyah Course Pare Kediri, analyze the causal factors, and formulate effective strategies to overcome these problems. The research method used is a qualitative approach with observation and interview techniques. The results of this study are that to overcome stereotypes and prejudices in multicultural education at the Naatiq International Arabiyah Course Pare Kediri, they not only adhere to knowledge and introduction to Arabic culture through the cultural introduction curriculum but also dare to speak and socialize with each other in discussions between classes to make it comfortable to learn without fear of making mistakes in pronouncing the language. So that Arabic language learning will be absorbed and cultural introduction will be more easily accepted. on the concept that differences in culture, ethnicity, and background are riches that enrich learning, not threats.